Vincanne Adams: Doctors for Democracy. Health Professionals in the Nepal Revolution - Samuelsen, Helle (Tidsskriftet Antropologi, 1998)
Vincanne Adams: Doctors for Democracy. Health Professionals in the Nepal Revolution. Anmeldes af Helle Samuelsen